Flowering and fruiting phenology of the fiber palm under the conditions of Belém, Pará, Brazil - Oliveira, Maria do Socorro Padilha de; Mendes, Gleidson Guilherme Caldas; Maciel, Alynne Regina Nazaré Alves; Costa, Jordan Brabo da (Research, Society and Development, 2024)
The objective of this work was to evaluate the reproductive phenology of fiber palm (Astrocaryum vulgare Mart.) cultivated in Belém, PA. Monthly monitoring was carried on 182 plants in full reproductive phase of the Active Germplasm Bank of Embrapa Amazon Eastern, during 36 months in three flowering and four fruiting events and their relationship with four meteorological variables. The occurrence rates of each event was determined per month, the activity index, the correlations between the phenophases and meteorological variables, the factor analysis and the phenogram. The events occurred in all years, but with small variations in the months for the beginning and end of the occurrence, with rates varying from 0.0 to 90%. The most regular event was bunches with green fruits. The peak of flowering occurred in the months of May, June and July and fruiting from January to March. Most events were mot very synchronous. Precipitation was the most important climatic factor in the reproductive phenology of this species. The results allow us to state that, under the conditions of the study, the fiber palm presents flowering events in the least rainy months and fruiting events in the rainiest months, being not very synchronous and with an annual phenological pattern.